Tinjauan Sosiologi Hukum terhadap Penyelesaian Talak di Bawah Tangan: Studi Kasus Desa Wakan Kecamatan Jerowaru Kabupaten Lombok Timur NTB - Islam, Ahmad Fikrul; Arifin, Zaenal (Jurnal Hukum dan Demokrasi (JHD), 2024)
This research is motivated by the findings of researchers in the field regarding the existence of secret divorce processes in Wakan Village, Jerowaru District, East Lombok Regency. In Wakan Village, there are many controversies surrounding the secret divorce settlement. In this study, the researcher aims to understand the process of secret divorce settlement among the community in Wakan Village and the impacts that arise from such secret divorces from a socio-legal perspective. The researcher utilized qualitative research in this study, collecting both primary and secondary data. Data collection techniques involved three stages: observation, interviews, and documentation. The data analysis conducted by the researcher is qualitative descriptive interpretation of the findings presented deductively (general). Subsequently, in the final conclusion, the researcher draws inductive (specific) and systematic conclusions. Keywords: Sociology of Law, Settlement of Divorce Under the Hand